Pencegahan Stunting dengan Inovasi Teknologi berupa Modifikasi Timbangan Digital Terkoneksi Android - Sudarsono, Bambang; Sukesi, Tri Wahyuni; Tentama, Fatwa; Mutmainah, Nur Fitri; Yuliansyah, Herman; Mulasari, Surahma Asti; Nafiati, Lu’lu’; Sulistyawati, Sulistyawati; Ghozali, Fanani Arief (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Stunting is a problem that has a negative impact on society and can last for a long time. This community service program aims to increase the knowledge and skills of partner communities in preventing stunting by using innovative technology called the "Tas Stunting Kit." This activity involves creating appropriate technology, training health cadres, and evaluating technological innovation. The digital scale is modified to connect to an Android tablet via Bluetooth and is packaged in a bag. This community service program was attended by 29 participants, all of whom were health cadres, with the implementing team consisting of the chief proposer, additional proposers, and a second team consisting of lecturers and students. This technological innovation was evaluated with the Software Usability Scale (SUS) as a series of modifications to digital scales and Android applications, with the results having an acceptable acceptability range. The subsequent follow-up is developing a more integrated data collection system as a basis for the village government to make data-based decisions.